STUDI PEMAHAMAN TERHADAP MASYARAKAT KOTA BUKITTINGGI TENTANG PRODUK BANK SYARIAH - Zulhelmi, Zulhelmi; Affandi, Ahmad Rajab (jurnal ekonomi, 2007)
By involving 163 respondents from various levels of society analytical descriptive analysis methode and polling instruments. From the 163 respondents that are obtained, it is concluded that the level os understanding of Bukittinggi's society about syariah banking is still low, this is proved by the value of absolute understanding of each group of respondenst, from research, it is nclude in understand category, where as 95 persons (58,28%) underdtand a little and 46 persons (28,88%) do not understand. This numbers at the same time answer the writers primary hypothesis that states that the presume over the level of Bukittinggi society's knowledge about the product od syariah bangking is low.